Cytogenetic analysis and FISH of terminal deletion of long arm of chromosome 9 in a patient with acute promyelocytic leukemia (2009)
ABSTRACT: Deletions of the long arm of chromosome 9, del(9)(q22), are rare aberrations specifically found in acute myeloid leukemia (AML). Yamamoto et al, 1999, reported the first case of acute promyelocytic leukemia (APL) with a terminal 9q deletion as a sole abnormality. Here we describe the second case with the same aberration, the patient, an eleven-years-old girl with APL. Chromosomal analysis by the Giemsa R-banding technique and FISH using BCR/ABL and PML/RARA probe on short-term cell cultures from bone marrow was performed. A deletion of a 9 chromosome, del(9)(q22) was detected. Deletions of 9q have been described in about 3% to 4% of the AML patients, especially in M1 and M2 myeloid leukemia. Sole 9q terminal deletions, are less common than interstitial ones and involve q21~q22 band predominantly. A recent study suggests that 9q deletion, even in the absence of t(15;17), shows a relatively good prognosis. However, our patient died during the treatment.